Impact of organic and inorganic fertilizers application on the phytochemical and antioxidant activity of Kacip Fatimah (Labisia pumila Benth) - Ibrahim, Mohd Hafiz; Jaafar, Hawa Z. E.; Karimi, Ehsan; Ghasemzadeh, Ali (MDPI, 2013)
A study was conducted to compare secondary metabolites and antioxidant activity of Labisia pumila Benth (Kacip Fatimah) in response to two sources of fertilizer [i.e., organic (chicken dung; 10% N:10% P2O5:10% K2O) and inorganic fertilizer (NPK green; 15% N, 15% P2O5, 15% K2O)] under different N rates of 0, 90, 180 and 270 kg N/ha. The experiment was arranged in a randomized complete block design replicated three times. At the end of 15 weeks, it was observed that the application of organic fertilizer enhanced the production of total phenolics, flavonoids, ascorbic acid, saponin and gluthathione content in L. pumila, compared to the use of inorganic fertilizer. The nitrate content was also reduced under organic fertilization. The application of nitrogen at 90 kg N/ha improved the production of secondary metabolites in Labisia pumila. Higher rates in excess of 90 kg N/ha reduced the level of secondary metabolites and antioxidant activity of this herb. The DPPH and FRAP activity was also highest at 90 kg N/ha. The results indicated that the use of chicken dung can enhance the production of secondary metabolites and improve antioxidant activity of this herb.